Factors associated with stunting among children aged 6-59 months in Bensa District, Sidama Region, South Ethiopia: unmatched case-control study - Temesgen Tafesse; Amanuel Yoseph; Kaleb Mayiso; Taye Gari (BMC, 2021)
Abstract Background Stunting remains one of the most common malnutrition problems among children in Ethiopia. Identifying the risk factors of stunting assists health planners to prioritize prevention strategies, and is a fundamental step for intervention. Therefore, this study aimed to assess factors associated with stunting among children aged 6-59 months in Bensa district, Sidama Region, South Ethiopia, 2018. Methods A facility-based unmatched case-control study was conducted from January 10 to March 10, 2018, on a sample of 237(79 cases and 158 controls) children aged 6-59 months with their respective mothers/caretakers. Data were collected using a structured, face-to-face interviewer-administered questionnaire and standard physical measurements. The data were entered into EP INFO version 7 and WHO Anthro software and analyzed using SPSS version 20. The variables were entered into the multivariable model using the backward stepwise regression approach. Multivariable logistic regression analysis was used to identify factors associated with stunting. Adjusted odds ratio (AOR) with 95% confidence interval (95%CI) and p-value <0.05 was used to declare the significance. Results Sex distribution was almost equal (Males = 52.3%, Females = 47.7%).The mean (standard deviation) age of cases and controls was 27.35 (±12.71) and 28.70 (±13.27) months respectively. The risk factors for stunting were diarrhea in the past two weeks (AOR = 2.71, 95% CI: 1.42-5.16), being male (AOR = 2.37, 95% CI: 1.224-4.59), inappropriate exclusive breastfeeding (AOR =2.07, 95%CI: 1.07-4.01), having less than or equal to three under-five children in the household (AOR = 2.18, 95%CI: 1.03-4.64), and mothers who had no formal education (AOR =3.28, 95%CI :1.56-6.924). Conclusions Diarrhea in the past two weeks, sex of a child, inappropriate exclusive breastfeeding, number of under-five children in the household, and mothers who had no formal education were the risk factors of stunting. Thus organized efforts aimed at focus on prevention of diarrhea as part of an overall public health strategy for improving child health and nutrition. Educating mothers/caretakers on the importance of exclusive breastfeeding should be considered. Moreover, mothers need to be encouraged to space birth between children through the use of family planning services.